2020
DOI: 10.1101/2020.01.14.904847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building thelacoperon: A guided-inquiry activity using 3D-printed models

Abstract: AbstractUndergraduate biology courses rely heavily on visual representation of information. Students view images of plants, animals, and microbes, interpret data presented in graphs, and use drawings to understand how cells and molecules interact in three dimensions. Traditional teaching approaches exclude students with visual impairments and disadvantage students with disabilities that affect their interpretation and processing of visual and spatial information as well as stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Our previous work demonstrated that Tactile Teaching Tools with Guided Inquiry Learning (TTT-GIL) can provide an effective approach to teaching complex topics in microbial molecular genetics in diverse student populations. Introduction of an interactive, 3D lac operon puzzle resulted in significant learning gains in both populations in which it was implemented, with a larger effect size in a genetics class at an underfunded minorityserving institution than in a microbiology class at an R1 primarily white institution (Gordy et al, 2020;Ramirez and Gordy, 2020). The inclusivity of TTT-GIL activities, which are created using Universal Design for Learning (UDL), along with their hands-on, game-like nature, suggest that they may be an effective way of teaching cellular and molecular immunology concepts even to younger students (Hall et al, 2003;Rose and Meyer, 2006;Burgstahler and Cory, 2010;Rappolt-Schlichtmann et al, 2012;Meyer et al, 2014;Ramirez and Gordy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrated that Tactile Teaching Tools with Guided Inquiry Learning (TTT-GIL) can provide an effective approach to teaching complex topics in microbial molecular genetics in diverse student populations. Introduction of an interactive, 3D lac operon puzzle resulted in significant learning gains in both populations in which it was implemented, with a larger effect size in a genetics class at an underfunded minorityserving institution than in a microbiology class at an R1 primarily white institution (Gordy et al, 2020;Ramirez and Gordy, 2020). The inclusivity of TTT-GIL activities, which are created using Universal Design for Learning (UDL), along with their hands-on, game-like nature, suggest that they may be an effective way of teaching cellular and molecular immunology concepts even to younger students (Hall et al, 2003;Rose and Meyer, 2006;Burgstahler and Cory, 2010;Rappolt-Schlichtmann et al, 2012;Meyer et al, 2014;Ramirez and Gordy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that active learning pedagogies promote student achievement in science, technology, engineering, and mathematics (STEM) courses (Haak et al, 2011;Freeman et al, 2014). In fact, active learning approaches have been particularly impactful for diverse students, to include persons excluded because of their ethnicity or race (PEERs; Beichner et al, 2007;Asai, 2020;Gordy et al, 2020;Kressler and Kressler, 2020;Theobald et al, 2020). While numerous active learning modules have been developed within the field of biology, more are needed to promote the success of diverse student populations.…”
Section: Introductionmentioning
confidence: 99%
“…The TTT-GI approach blends both the use of tactile teaching tools (TTT) and guided inquiry (GI) learning. The use of TTT enhances student learning through manipulation of 3D models (Cooper and Oliver-Hoyo, 2017;Howell et al, 2018;Newman et al, 2018;Gordy et al, 2020;Ramirez and Gordy, 2020). Development of TTT typically involves either commonly available objects, such as craft supplies (DeBruyn, 2012;Mayorga et al, 2012;Gehret, 2017), or the use 3D printed objects (Howell et al, 2019;Kerwin, 2019;Gordy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations